Efficacy and tolerability of saxagliptin compared with glimepiride in elderly patients with type 2 diabetes: a randomized, controlled study (GENERATION). Issue 7 (7th April 2015) - Schernthaner, G.; Durán‐Garcia, S.; Hanefeld, M.; Langslet, G.; Niskanen, L.; Östgren, C. J.; Malvolti, E.; Hardy, E.
<x xml:space="preserve">Abstract</x> Aims To assess the efficacy and safety of adjunctive saxagliptin vs glimepiride in elderly patients with type 2 diabetes (T2D) and inadequate glycaemic control. Methods In this multinational, randomized, double‐blind, phase IIIb/IV study (GENERATION; NCT01006603), patients aged ≥65 years were randomized (1 : 1) to receive saxagliptin 5 mg/day or glimepiride ≤6 mg/day, added to metformin, during a 52‐week treatment period. The primary endpoint was achievement of glycated haemoglobin (HbA1c) <7.0% at week 52 without confirmed/severe hypoglycaemia. The key secondary endpoint was incidence of confirmed/severe hypoglycaemia. Safety and tolerability were also assessed. Results Of 720 patients randomized (360 in each treatment group; mean age 72.6 years; mean T2D duration 7.6 years), 574 (79.8%) completed the study (saxagliptin 80.3%; glimepiride 79.2%). Similar proportions of patients achieved the primary endpoint with saxagliptin and glimepiride (37.9 vs 38.2%; odds ratio 0.99, 95% confidence interval 0.73, 1.34; p = 0.9415); however, a significant treatment‐by‐age interaction effect was detected (p = 0.0389): saxagliptin was numerically (but not significantly) superior to glimepiride for patients aged <75 years (39.2 vs 33.3%) and numerically inferior for patients aged ≥75 years (35.9 vs 45.5%). The incidence of confirmed/severe hypoglycaemia was lower with saxagliptin vs glimepiride (1.1 vs 15.3%; nominal p < 0.0001). Saxagliptin was generally well tolerated, with similar incidences of adverse events compared with glimepiride. Conclusion As avoiding hypoglycaemia is a key clinical objective in elderly patients, saxagliptin is a suitable alternative to glimepiride in patients with T2D aged ≥65 years.